Concept of construction of information system of aviation technique maintenance - Салимов, P. M.; Масюк, И. И.; Зыков, О. С. (Proceedings of National Aviation University (archive), 1999)
Analysed are problems of automatic information provision of control of technical maintenance support. Also performed are the aims of provision of automatic information support. Presented are the requirements to the information system as a whole and to its components in particular. Considered is also contradictory connection between the necessity to simplify the abonent of interface of automated information and control system on the one hand, and to complicate the software on the other hand